Assessing and Impressing: A Guide for Medical School Seniors Who Are Applying for a Family Medicine Residency - Amanda Kost; Jane Huntington; Jeanne Cawse-Lucas (Association of American Medical Colleges, 2013)
Abstract Introduction The residency application process can be daunting for medical students and for those advising them. Many medical school seniors begin the process with an overwhelming number of questions. Medical student advisors, who may also be residency faculty, are charged with advising and mentoring students as they negotiate the process of helping students confirm specialty choice, realistically assess their competitiveness, search for compatible programs, submit the application, prepare for the interview day, and ultimately rank and matching into a program where they will thrive. At the University of Washington Department of Family Medicine, we designed a comprehensive advising strategy that includes a LISTSERV, group meetings at key times, individual advisors for students, and mock interviews. We also developed written information for every step of the process of applying for residency in family medicine, and that is what we are sharing here. Methods This resource is an evidence-based toolkit of written material divided into three sections. The first section, Assessing, helps students systematically evaluate their competitiveness and what they want from residency training. The second section, Impressing, offers students information about how to best present themselves to programs, including tips for interview day. The third section, Putting It All Together, helps students review programs and develop a rank list. Sections can be printed and given to students, presented online, or used in group or individual advising sessions. Results We surveyed 40 students who used these materials and matched in family medicine in May 2012. Eleven students rated their overall preparedness for the residency application process as a 4.77 on a 5-point scale. Students rated the helpfulness of these written materials (4.82) as being almost the same as a person advising (4.83). Discussion We believe that students who have an approach for assessing their own competitiveness, assessing potential residency programs, and then for impressing the programs where they apply and interview will be more likely to match at programs that meet their training goals. This is an obvious advantage for both students and residency programs, and it makes the work of medical student advisors more enjoyable and rewarding. This resource can be generalized to other schools, and possibly to other specialties.